A ring D chromosome in association with Down's syndrome-like phenotype - A. Wajntal; A. J. Diament; P. H. Saldanha (Arquivos de Neuro-Psiquiatria)
The case of a ten-years-old mentally retarded girl with Down's syndrome-like features whose chromosome analysis revealed an unusual mosaicism including 10% mitosis with a ring chromosome replacing a D chromosome is reported. The clinical features of the patient were considered similar to those described by Jacobsen (1966) and Emberger et al. (1971) who interpreted the ring chromosome present in their patients as being chromosome 15.